ALBERT SCHWEITZER’S ETHIC OF REVERENCE FOR LIFE AS AN EDUCATIONAL IDEAL - Blackwell, David (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1970)
Little or no attempt has been made in the English-speaking world to consider the possible significance for educational thought and practice of the late Albert Schweitzer’s ethical principle of "Reverence for Life." Thus, the main purpose of this paper is to indicate the relevance for education of an ethic that claims to provide a worthy ideal, that of the civilized man.